MODEL PENGAJARAN MOTIVASI DAPAT MENGATASI SPEECHLESS PESERTA DIDIKDALAM KBM BAIK DARI SD HINGGA UNIVERSITAS - Mafruhah, Mafruhah (Fakultas Agama Islam Universitas Islam Madura, 2019)
In a learning process at a class, a teacher or lecture need a model learning in order to solving the speechless character (dump, stuttering, or stammering) like is afraid or pasif character is in personality of student, like is student or scholarship. Cause that character usually happen since primary school like SD or MI and than in high school too, like in junior high school and senior high school. After that, the it character was bring along until univerity. The learning model was suitable for solving that problem is motivation model. By motivator, a teacher or lecture can solve the speechless become speechness so the student or scholar can activ, confident, and bravo to performance in front of class.